A 3D image analysis of intermetallic inclusions. (22nd September 2009) - Parra-Denis, Estelle; Ducottet, Christophe; Jeulin, Dominique
The problem of 3D shape characterisation has been intensively studied lately, because computing power is greatly increasing and image acquisition is more efficient, with new real 3D image acquisition methods like microtomography. The material studied in this work is a 5xxx aluminium alloy. It contains intermetallic particles which control both formability and surface aspect. During the industrial process used to transform slabs into plates, particles are broken and redistributed in the sheet space. In this paper, the shape of the intermetallic particles originating from the solidification process of aluminium alloys is studied. These particles are observed as being very complex. Modelling their shape requires a single approach based on 3D morphological analysis. A description of the shape of each intermetallic particle is given, using parameters and distribution measures. This paper also presents an original way to study the evolution of particles at different stages of deformation of the material and the evolution of its orientations.